PENGGUNAAN METODE TERPIMPIN DALAM KEMAMPUAN MENULIS CERITA PENDEK SISWA KELAS X SMK SWASTA ERIA MEDAN TAHUN PEMBELAJARAN 2021-2022 - Muliani Sinaga, Endang Sri (Jurnal Bahastra, 2022)
Short story is one part of literary works in the form of prose. Short stories or short stories, which are more popular with the acronym short story, are one of the most popular types of fiction written by people. This study aims to determine the ability of class X students of Eria Private Vocational School Medan in the 2021-2022 learning year in writing short stories. The population in this study were all students of class X SMK Private Eria Medan, totaling 38 students with reasons below 100, so the sample was from the entire population. The research design used in this study was a quasi-experimental design. By using a research design of one group pre-test and post-test design group. The instrument used is an essay test to write short stories. The average value before using the guided method was 65.60, while the average value after using the guided method was 79.71. Thus it is said that the test score using the guided method is higher than before using the guided method. Based on the data above, it can be concluded that the guided method has a positive effect on the ability of class X students at the Eria Private Vocational School in Medan for the 2021-2022 academic year in writing short storiesShort story is one part of literary works in the form of prose. Short stories or short stories, which are more popular with the acronym short story, are one of the most popular types of fiction written by people. This study aims to determine the ability of class X students of Eria Private Vocational School Medan in the 2021-2022 learning year in writing short stories. The population in this study were all students of class X SMK Private Eria Medan, totaling 38 students with reasons below 100, so the sample was from the entire population. The research design used in this study was a quasi-experimental design. By using a research design of one group pre-test and post-test design group. The instrument used is an essay test to write short stories. The average value before using the guided method was 65.60, while the average value after using the guided method was 79.71. Thus it is said that the test score using the guided method is higher than before using the guided method.Based on the data above, it can be concluded that the guided method has a positive effect on the ability of class X students at the Eria Private Vocational School in Medan for the 2021-2022 academic year in writing short stories